Prospectivity of Batinah Coast of Oman for Volcanic Hosted Massive Sulfide (VHMS) Deposits - Yadav, P.K (IJRDO - Journal of Social Science and Humanities Research, 2016)
Central and south Batinah coastal areas are mostly covered with rocks of Hawasina and Samail nappes obducting over autochthnous Formations of Arabian plate. Hawasina nappe is composed of late Permian to Jurassic Formations comprising sandstone, shale, chert, limestone, basalt, andesite and keratophyre. Samail nappe is thrust over the Hawasina nappe and composed of complete ophiolite suite of rocks. Samail volcanic sequence hosts Cu-Au-Ag mineralisation (VHMS) and forms uppermost part of Samail ophiolite sequence. Copper deposits of Oman have supplied copper metal over a span of ancient time to Sumerian and Roman empires Samail volcanic unit shows three major events of basaltic effusion namely they are Lower Volcanics (SV1), Middle Volcanics (SV2) and Upper Volcanics (SV3). All the units show intercalated thin metalliferous sedimentary chert/shale layers deposited during pause of eruptive active. Post nappe formations consist of Upper Cretaceous and Tertiary Formations composed of polymict conglomerate, marl and limestone. These are covered by Quaternary sediments comprising terrace and fan deposits called wadi sediments. Tectonic developments of Samail Nappe were in different stages. Stage-1 included formation of Samail ophiolite on the sea floor, stage-2 included obduction of Samail ophiolite and stage-3 contains post emplacement deposition of younger cover sediments. Samail ophiolite was formed in the spreading ridge of Tethys sea from Early to Middle Cretaceous period (92-97 Ma). During this stage Hawasina basin was formed and subsequently obduction took place in deposits. They form from metal rich fluids associated sea floor hydrothermal convection system.